The N‐Acetylgalactosamine‐conjugated small interfering RNA inclisiran can be coadministered safely with atorvastatin in cynomolgus monkeys resulting in additive low‐density lipoprotein cholesterol reductions - Dario Lehoux; David Kallend; Peter L. J. Wijngaard; Alan P. Brown; Brad Zerler (Wiley, 2023)
Abstract Inclisiran, a small interfering RNA, selectively inhibits proprotein convertase subtilisin/kexin type 9 (PCSK9) synthesis in the liver and has been shown to reduce low‐density lipoprotein cholesterol (LDL‐C) by ≥50% in patients with hypercholesterolemia receiving maximally tolerated statins. The toxicokinetic, pharmacodynamic, and safety profiles of inclisiran when coadministered with a statin were characterized in cynomolgus monkeys. Six cohorts of monkeys were administered either atorvastatin (40 mg/kg, reduced to 25 mg/kg during the study, daily, oral gavage), inclisiran (300 mg/kg every 28 days, subcutaneous administration), atorvastatin (40/25 mg/kg) and inclisiran combinations (30, 100, or 300 mg/kg), or control vehicles over 85 days followed by 90 days' recovery. Inclisiran and atorvastatin toxicokinetic parameters were similar in cohorts administered either agent alone or in combination. Inclisiran exposure increased in a dose‐proportional manner. At Day 86, atorvastatin increased plasma PCSK9 levels four‐fold from pretreatment levels but did not significantly lower serum LDL‐C levels. Inclisiran (alone or in combination) reduced PCSK9 (mean decrease 66-85%) and LDL‐C (mean decrease 65-92%) from pretreatment levels at Day 86; levels were significantly lower than the control group (p ≤ .05) and remained decreased during the 90‐day recovery. Coadministration of inclisiran with atorvastatin resulted in greater reductions in LDL‐C and total cholesterol compared with either drug alone. No toxicities or adverse effects were observed in any cohort receiving inclisiran, either alone or in combination. In summary, inclisiran significantly inhibited PCSK9 synthesis and decreased LDL‐C in cynomolgus monkeys without increasing the risk of adverse effects when coadministered with atorvastatin.